Defining Ship Principal Dimensions Using Comparison Method - Renanda Bayu Harsi; Nuzulul Arif (Institut Teknologi Adhi Tama Surabaya, 2021)
AbstractIn the process of finding the principal dimension of the ship there are various methods that can be used. In this study, the Comparison method will be used to obtain the main size of the ship and the main dimensions of the ship are obtained, namely, length (L) = 20,152 meters, beam (B) = 5.5 meters, depth (H) = 2,939 meters, draft (T) = 1.5129 meters, service speed (Vs) = 20 knots. The ship's resistance is 152.6 kN at service speed (Vs) = 20 knots. And can be overcome with a power of 2426.31 HP. The power taken to meet these needs is 2500 HP supplied by 2 outboard engines with a power of 1300 HP each.Keywords : Comparison Method.